2014
DOI: 10.1111/phn.12133
|View full text |Cite
|
Sign up to set email alerts
|

Core Competency Model for the Family Planning Public Health Nurse

Abstract: Competencies with at least 75% consensus were included in the model and those competencies were primarily related to education/counseling and administration of medications and contraceptives. The competencies identified have implications for education/training, certification and workplace performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 7 publications
2
20
0
1
Order By: Relevance
“…It provides an effective framework for nurses and managers to evaluate, train and practice required work-related competencies. 16 Studies have indicated that core competence is necessary for nurses to provide safe and high quality of care in their clinical services, and furthermore, that a competent nursing workforce is critical to the success of national healthcare systems. 17 To date, numerous studies have been conducted to clarify core competence required for specific nursing roles and to develop corresponding evaluation measures.…”
Section: Core Competence As a Predictor Of Voice Behaviormentioning
confidence: 99%
“…It provides an effective framework for nurses and managers to evaluate, train and practice required work-related competencies. 16 Studies have indicated that core competence is necessary for nurses to provide safe and high quality of care in their clinical services, and furthermore, that a competent nursing workforce is critical to the success of national healthcare systems. 17 To date, numerous studies have been conducted to clarify core competence required for specific nursing roles and to develop corresponding evaluation measures.…”
Section: Core Competence As a Predictor Of Voice Behaviormentioning
confidence: 99%
“…It can be concluded that this ability can be improved from work experience; the longer the community nurse experience works, the better the ability of communication and financial management in the community will be. Different from the management and planning skills, although specifically nurses have a branch of nursing management (Cross et al, 2006;Hewitt, Roye, & Gebbie, 2014;Polivka & Chaudry, 2015), but the theory is more appropriate to use by nurses in clinical settings, not in the community. .…”
Section: Resultsmentioning
confidence: 99%
“…In the provision of care domain, competences were identified for work in reproductive planning, pre-conception, prenatal, assistance in delivery and care in climacteric period, as well as provision of actions, counseling, choice of diagnosis, problem solving in face of sexual dysfunctions and technical qualification for clinic care. Such competences were considered fundamental for qualification of care provided in sexual and reproductive health in the ambit of primary healthcare [15][16][17] , and necessary for sexual and reproductive health care practice 1 .…”
Section: Resultsmentioning
confidence: 99%
“…International literature documents and studies on these competences address the need of formation on competences to act in the sexuality area through the proposal of a training program for clinical assessment of sexual and reproductive health for professionals in primary healthcare 11 ; the need to train nurses to work in sexual and reproductive health 12 ; assessment of knowledge on these issues with physicians in Pakistan 13 ; barriers and challenges found by primary healthcare professionals to provide counseling and assistance in reproductive planning 14 . In this same context, competences were identified for physicians, nurses and pharmacists in primary healthcare to subsidize these professionals' actions in SRH 15 and for public health nurses associated to family planning contemplating educational aspects and anti-conception counseling 16 .…”
Section: Introductionmentioning
confidence: 99%